Reaktualisasi Dharma Dakwah Islamiyah Kampus UII Demangan Baru1 - Ahmad Darmaji; Syarief Zudaidah; Yusdani Yusdani; Edi Safitri (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2014)
The following research tries to answer the research question of how the portrait and the dynamics of society around campus of UII Jalan Damangan Baru No. 24 Yogyakarta? and how social dynamics of society from the perspective of Islamiyah Dakwah as one of the dharma UII? This research is a field and qualitative research, the location of research at Campus UII Jalan Damangan Baru No. 24 Yogyakarta. The approach that used in this study is phenomenological approach. The analysis which used in this study is the analysis of Miles that including: data reduction, data display and conclusion drawing / verification as an intertwined at the time before, during, and after the collection of data in parallel, to build conclusion. The results of this research has been revealed that the religious community in Campus UII Jalan Demangan Baru emphasizes tolerance. However, the attitude of this potential, by the Campus UII has never seen as an opportunity to do various efforts to strengthen through service programs and Islamiyah Dakwah. In addition to this research also found that the relationship between the Campus UII Jalan Demangan Baru with itys several units and the local community, not shown as partners of both planned and programmed for mutual support and cooperation between two entites. Keywords: dakwah, Universitas Islam Indonesia, religious life, lembaga pendidikan Islam Islam.